1998
DOI: 10.1161/01.str.29.6.1219
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Cyclooxygenase Expression in Canine Basilar Artery After Experimental Subarachnoid Hemorrhage

Abstract: Background and Purpose —Inducible cyclooxygenase (COX-2) has been found to play a pathological role in cerebral insult . We investigated the expression of COX-2 in the basilar artery after experimental subarachnoid hemorrhage (SAH). Methods —In a canine “two-hemorrhage” model of SAH, the basilar arteries were obtained on day 2 after a cisternal injection of autologous blood or on days 4, 6, 7, or 9 after the second injection. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 44 publications
0
19
2
Order By: Relevance
“…In the cerebral arteries COX-2 is expressed constitutionally (113), but its overexpression after SAH has been little studied. In an immunohistochemical study, it was found only in the endothelial layer 3 days after SAH (91), although a previous immunoblot study showed its overexpression in the arteries after 2 days (114). In our study (91), the expression of COX-2 was preceded during day 1 by a rise in the CSF concentration of TNF-a .…”
Section: The 5-lipoxygenase Pathway and Ltscontrasting
confidence: 52%
See 2 more Smart Citations
“…In the cerebral arteries COX-2 is expressed constitutionally (113), but its overexpression after SAH has been little studied. In an immunohistochemical study, it was found only in the endothelial layer 3 days after SAH (91), although a previous immunoblot study showed its overexpression in the arteries after 2 days (114). In our study (91), the expression of COX-2 was preceded during day 1 by a rise in the CSF concentration of TNF-a .…”
Section: The 5-lipoxygenase Pathway and Ltscontrasting
confidence: 52%
“…These findings suggest that IL-1b is a powerful molecule acting at very low concentrations. Intracisternal injection of cytokines (0.03 mg IL-1b, 3 mg IL-6 or 10 mg IL-8) induce COX-2-immunoreactive protein in the basilar artery (114).…”
Section: Il-1mentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation of COX-2 in the cerebral arteries after SAH has been previously described (42,43,53). COX-2 produces a variety of vasoactive prostanoids as well as superoxide anion that may have affected the baseline diameter as well as the responsiveness of the basilar artery to both acetylcholine and cromakalim.…”
Section: Discussionmentioning
confidence: 72%
“…The release of prostaglandins is part of the inflammatory response and may mediate tissue inflammation or anti-inflammatory effects (21). COX-2 expression was detected in basilar arterial tissue in both acute and chronic stages following SAH (22). Therefore, PGES may, in turn, produce sufficient quantities of eicosanoids to affect hemodynamics following SAH.…”
mentioning
confidence: 99%